1997
DOI: 10.1089/hyb.1997.16.33
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Responses to the Tumor-Associated Antigen CA15 in Patients with Advanced Ovarian Cancer Induced by the Murine Monoclonal Anti-idiotype Vaccine ACA125

Abstract: We have generated an immunoglobulin G1 (IgG1) murine monoclonal anti-idiotype antibody (Ab2) designated ACA125, which mimics a specific epitope on the tumor-associated antigen CA125. This antigen is expressed by most of malignant ovarian tumors. Patients with CA125-positive tumors are immunologically tolerant to CA125. We used ACA125 as a surrogate for the tumor-associated antigen CA125 for vaccine therapy of 16 patients with advanced epithelial ovarian cancer or recurrences. Each of the patients received a mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 10 publications
1
25
0
Order By: Relevance
“…This antibody functionally mimics the CA125 antigen and induces humoral and cellular CA125-specific immunity (11). In previous studies, the antiidiotypic antibody has been shown to induce immune reactivity against CA125-expressing tumors by induction of specific antianti-idiotypic antibodies (also called Ab3; refs.…”
mentioning
confidence: 99%
“…This antibody functionally mimics the CA125 antigen and induces humoral and cellular CA125-specific immunity (11). In previous studies, the antiidiotypic antibody has been shown to induce immune reactivity against CA125-expressing tumors by induction of specific antianti-idiotypic antibodies (also called Ab3; refs.…”
mentioning
confidence: 99%
“…30 OVCA cells express mutated forms of p53 [31][32][33] and/or BRCA-1 34,35 tumor suppressor genes. Ovarian tumor cells also express high levels of the CA-125 [36][37][38] and MUC1 39 TAA. In addition, these tumors express abundant levels of the HER2/neu (c-erB2) and epidermal growth factor receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, patients with cytotoxic T-cells (CTLs) against MUC16 had a better clinical prognosis regardless of whether they received therapy, suggesting the importance of MUC16 in ovarian cancer [49]. Other than monoclonal antibodies, studies have also investigated the use of vaccinations such as the ACA125 vaccine, which showed a 3-month improvement in progression free survival in patients with advanced ovarian cancer [50,51]. Similarly, another preclinical study investigating a MUC16 vaccine showed that patients generated an IgG response, however the clinical utility is yet to be determined [52].…”
Section: Anti-muc16 Antibodiesmentioning
confidence: 99%